Functional outcome of displaced femoral neck fractures in young patients treated by dynamic hip screw with CC screws - Mahadik, Sujay; Singh, Chandra Prakash; Phule, Akshay; Kheni, Nikunjkumar; Deshpande, Shrikant (Asian Journal of Medical Sciences, 2022)
Background: Although femoral neck fractures are common in elderly individuals, it is an uncommon occurrence in young patients. It is crucial to achieve anatomical reduction as well as stable fixation so as to avoid complications in young individuals who are expected to have considerable functional demand in post-surgical period. Dynamic hip screws are commonly used for internal fixation of these fractures. Although satisfactory functional outcomes have been reported in the patients treated by DHS, complications such as malunion and osteonecrosis remain an area of concern. Aims and Objectives: The aims of the study were to study the functional outcome of young patients with femoral neck fractures treated by DHS with CC screws and to study the complications in young patients with femoral neck fractures treated by DHS with CC screws. Materials and Methods: This was a prospective cohort study in which 80 young adults (below the age of 45 years) having femoral neck fractures and treated by DHS with 2CC screws were included in this study on the basis of a predefined inclusion and exclusion criteria. Gender and distribution, nature of injury, type of fracture, functional outcome, and complications were studied in studied cases. Open reduction and internal fixation was done using dynamic hip screw. The functional outcome was assessed using modified Harris hip score. All patients were assessed for complications such as non-union, malunion, and osteonecrosis. Statistical analysis was done using SSPS 21.0 software and P<0.05 was taken as statistically significant. Results: Out of 80 studied cases having femoral neck fractures, there were 54 (67.50%) males and 26 (32.50%) females with an M: F ratio of 1:0.48. The mean age of male and female patients was found to be 38.37±4.62 and 38.80±4.97 years, respectively. The most frequent cause of fracture was fall from height (48 cases) followed by road traffic accident (31 cases). Forty-six patients had complete fracture with partial displacement (Type III) and remaining 34 patients had complete fracture with total displacement (Type IV). Associated injuries were seen in 9 (11.25%) patients. Nine (11.25%) cases of avascular necrosis of femoral head were seen in our study. Surgery more than 48 h after injury and complete fracture with total displacement were associated with increased risk of avascular necrosis of femoral head (P<0.05). Conclusion: Femoral neck fractures in young patients treated by dynamic hip screws with CC screws have found to have excellent functional results in majority of cases. The complications such as osteonecrosis of femoral head can be minimized by decreased time duration between fracture and surgical intervention.